Pidana Bersyarat Perspektif Kitab Undang-Undang Hukum Pidana Dan Fikih - Abidin, Moch Zainal (Al-Jinayah: Jurnal Hukum Pidana Islam, 2015)
Abstract: This study aims to assess conditional criminal act in Criminal Code and Islamic jurisprudence. Conditional criminal act according to Criminal Code is a kind of crime where the convict does not have to undergo the punishment, except he has violated the general or specific requirenments of court during pre-determined. On the Islamic jurisprudence perspective, conditional criminal act is caterized as diyÃ¢t and taâzÃ®r. DiyÃ¢t is a kind of criminal penalty that provides a number of property within a certain size, given by the offender to the victim or his heirs. While taâzÃ®r is a legal authority delegated by state to a judge to decide the criminal cases. In taâzÃ®r, a judge has fairly broad authority to choose any types of crime that are appropriate to the circumstance of the offense and the perpetrators. Looseness or facilities provided to a judge do not reduce the initial goal of punishment as an attemp to improve the criminal actors in order to keep the benefit of people.Keywords: Conditional criminal act, Criminal Code, Islamic jurisprudence.Â Abstrak: Artikel ini mengkaji tentang pidana bersyarat dalam Kitab Undang-Undang Hukum Pidana dan fikih. Pidana bersyarat menurut Kitab Undang-Undang Hukum Pidana, merupakan suatu pidana di mana terpidana tidak usah menjalani pidana tersebut, kecuali bilamana selama masa percobaan terpidana telah melanggar syarat-syarat umum atau khusus yang telah ditentukan oleh pengadilan. Jika dianalisis dari sisi fikih, pidana bersyarat dikatagorikan masuk dalam diyÃ¢t dan taâzÃ®r. DiyÃ¢t merupakan suatu jenis pidana yang memberikan sejumlah harta dalam ukuran tertentu, yang diberikan pelaku tindak pidana kepada korban atau ahli warisnya. Sedangkan taâzÃ®r merupakan kekuasan dalam memutuskan suatu perkara diserahkan kepada negara dan selanjutnya diserahkan kepada hakim. Di dalam taâzÃ®r ini, hakim mempunyai wewenang yang cukup luas untuk memilih jenis pidana yang sesuai dengan keadaan tindak pidana serta diri pelakunya. Kelonggaran atau kemudahan yang diberikan kepada hakim tidak mengurangi tujuan awal dalam setiap pemidanaan, sebagai wujud memperbaiki diri pelaku demi terjaganya kemaslahatan di dalam masyarakat.Kata Kunci: Pidana bersyarat, Kitab Undang-Undang Hukum Pidana, fikihÂ